THE CORRELATIONS AMONG THE COMPLEX OF SPINE-PELVIS TRAITS AND THE FEET TRAITS IN BOYS AGED 4 TO 6 YEARS - Mirosław Mrozkowiak; Mariusz Posłuszny; Hanna Żukowska; Sergii Iermakov; Mirosława Szark-Eckardt (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: Early diagnosis is one of meaningful elements of prevention and treatment of postural defects. The objective of the study was an attempt to determine the correlations among the spine - pelvis traits and the feet traits in the population of boys aged 4 to 6 years living in rural areas and cities. Material and method: The study group covered 1506 boys aged 4 to 6 years. The measurement of 104 traits of the spine-pelvis and feet complex was conducted by means of the projection Moiré method for computer-based examination of body posture. Results: there is not much publications on the influence and correlations between the complex of the pelvis-spine traits and the feet traits. There is a correlation between the forming foot type and formation of the spine. The proposed Steinmetz suggestion assuming that if the spine can be corrected with the foot then the foot can be corrected by means of the spine, raises a number of doubts. The author emphasizes the meaning of wearing corrective footwear since proper foot positioning provided by special shoes cannot be the cause of spinal deformities. Conclusions: The spine-pelvis trait in the population of boys most frequently revealing significant influence on the feet traits is the height and depth of thoracic kyphosis. The foot trait among the population of boys living in cities most frequently revealing significant influence on the spine-pelvis traits was the value of the right foot length. In the rural population significant influence on the spine-pelvis traits was revealed by: the length and height of the fifth longitudinal arch of the left foot.